The Influence of Export and Import Activities on Economic Support in the Aceh Region - Rahmah Hayati; Arif Rifaldi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The progress of a country, based on increased economic growth, was calculated from added total production to the service and commodity for economic activity. It increased the income per capita in the population of the region. The financial system would report with specificity goods production also services. Then, it occurred wherein a more extensive market production accommodation exists market conducts the trade international system. The research aimed to determine the activity exports are also importing to support the Aceh area's economy. A study used the method of quantitative. Furthermore, results showed an increase in foreign trade to the trade balance, indicating the commodity for foreign economics. Based on the analysis using the Eviews-12 method, exports, and imports affected the economic growth in Aceh. The total volume of imports increased from 20,489,210 kg to 20,281,743 kg from January to December 2016, but there was an increase in the CIF value from 2,184,788 US$ to 9,034,788 US$, that the volume of imports of economic goods in 2019 from January was 14,244,916 kg, with an export value of 2,438,041 US$. Furthermore, it was positively controlled for export. The total imports of Aceh Province were found the fluctuations that occurred in 2016, 2019, and 2022. The highest amount of substances in 2016 was 7,612,298, and the lowest in 2022 was 8,192,390. The trade balance of Aceh Province showed a positive value, then the foreign trade of the economic commodity was dominated for export activities. Although in three long-term decades, exports have been reported to have a positive growing financial effect, whereas the activity of import and role to lowest roles growing economy. Then, in a short time, other export has less impact on economic growth than imports. Furthermore, the economic growth would be finished to increase the imports and commodities or materials exports to industrial needs.